"CULTIVATING A GREENER TOMORROW: THE POWER OF ORGANIC FARMING IN JAMMU AND KASHMIR" - Ishfaq Ahmad Mir; Irshad Ahmad Reshi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Abstract Organic farming is a method of farming in which the use of chemical fertilisers, pesticides, herbicides, and growth hormones is restricted to a large extent, and soil fertility is maintained through the use of organic manures, green manures, crop rotation, etc. The purpose of this study is to highlight the role of organic farming in enhancing agricultural sustainability in Jammu and Kashmir. Organic farming is a sustainable method that attempts to utilize as little artificial input as possible and as much of the environment's natural resources as possible. The study examines the situation of organic farming practices in Jammu and Kashmir, looking at how they affect the health of the soil, the availability of water, biodiversity, and farmer livelihoods. The study's key findings indicate that organic farming has the potential to improve agricultural sustainability by boosting soil fertility, saving water resources, maintaining biodiversity, and delivering economic advantages to farmers. The study also examines market access, legislative assistance, public awareness initiatives, and obstacles and possibilities related to the adoption of organic farming in Jammu and Kashmir. Overall, the study highlights the relevance of organic farming as a sustainable agricultural practise that may improve the long-term welfare of farmers and the environment in Jammu and Kashmir.